2003
DOI: 10.1364/ol.28.000716
|View full text |Cite
|
Sign up to set email alerts
|

Second-harmonic generation from ellipsoidal silver nanoparticles embedded in silica glass

Abstract: Second-harmonic generation of uniformly oriented, ellipsoidal silver nanoparticles in a glass matrix was observed and investigated as a function of incidence angle, light polarization, and spatial arrangement of the particles. The results can be explained by the symmetry of the spatial nanoparticle arrangement and by resonance enhancement that is due to the localized surface plasmons of the particles. Second-harmonic enhancement is observed only in sufficiently thin layers (deltakl < pi); on a sample with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(41 citation statements)
references
References 13 publications
1
40
0
Order By: Relevance
“…Experimentally, the enhancement of second-harmonic generation at rough metal surfaces has been observed using both far-field [55][56][57][58] and near-field 59,60 spectroscopic techniques, with measured enhancements of second-harmonic generation on Au and Ag island films up to 1000. 58 While the magnitude of the reported enhancement varies considerably, recently direct observations of localized second-harmonic enhancements of order 1000 have been reported on Au surfaces coated with random scatterers using laser scanning microscopy.…”
Section: Local Field Enhancement Around Metal Nanoparticle Structumentioning
confidence: 97%
“…Experimentally, the enhancement of second-harmonic generation at rough metal surfaces has been observed using both far-field [55][56][57][58] and near-field 59,60 spectroscopic techniques, with measured enhancements of second-harmonic generation on Au and Ag island films up to 1000. 58 While the magnitude of the reported enhancement varies considerably, recently direct observations of localized second-harmonic enhancements of order 1000 have been reported on Au surfaces coated with random scatterers using laser scanning microscopy.…”
Section: Local Field Enhancement Around Metal Nanoparticle Structumentioning
confidence: 97%
“…11 Enhancements as large as 10 7 have been reported in nanoparticle clusters, enabling, for example, Raman spectroscopy of single molecules. 12,13 Other than Raman spectroscopy, [14][15][16] this phenomenon has found applications in optical third-harmonic generation, [17][18][19] as well as in second-harmonic generation, [20][21][22][23][24][25][26] which is the subject of this paper. Nahata et al 23 demonstrated an ∟10 4 -fold increase in the efficiency of optical second-harmonic generation from concentric silver ring structures centered around a 200-nm aperture (bull's-eye structure) compared to a silver film with an unadorned aperture.…”
mentioning
confidence: 99%
“…Nahata et al 23 demonstrated an ∟10 4 -fold increase in the efficiency of optical second-harmonic generation from concentric silver ring structures centered around a 200-nm aperture (bull's-eye structure) compared to a silver film with an unadorned aperture. Podlipensky et al 24 observed second harmonic generation (SHG) enhancement from ellipsoidal silver nanoparticles in a glass matrix grown by means of Ag + -Na + ion exchange. More recently, Moran et al 25 have demonstrated second harmonic excitation spectroscopy of silver nanoparticle arrays, which were fabricated by nanosphere lithography.…”
mentioning
confidence: 99%
“…al. (Podlipensky et al, 2003) on elongated Ag NPs. The main differences with respect to our experiments are that this group obtained equivalent intensities for both p-and s-SH signal and no measurable signal for spherical NPs was detected.…”
Section: Resultsmentioning
confidence: 99%
“…For materials composed of nonlinear optical scatterers much smaller than the wavelength of the fundamental beam, such as in the case of thin films composed of syntectic macromolecules or fibrillar proteins for instance (Knoesen et al, 2004;Leray et al, 2004;Podlipensky et al, 2003;Rocha-Mendoza et al, 2007), the origins of the bulk second-order susceptibility  2 ijk  comes from the coherent summation of the molecular hyperpolarizability ''' i j k  of the smaller molecules. In a similar way, due to the fact that the elongated NPs of our samples are at least a hundred times smaller than the wavelength of the fundamental light and in the limit of weak coupling between each nonlinear NP, we can express the macroscopic susceptibility of the thick layer containing NPs as…”
Section: Theoretical Analysismentioning
confidence: 99%